THE VISUAL IMAGES OF ENGLISH FOR MARITIME VOCATION TEXTBOOK - Tawrofie, Nindi Assabila; Murtafi’ah, Banatul (Journal of English Educational Study (JEES), 2025)
This study aims to identify the types of visual images in English for Specific Purposes (ESP) of English for Maritime Vocation. This research used a qualitative research method using content analysis. The researchers used Kress and van Leeuwen's (2006) Visual Grammar framework to analyze the visual design from English in Maritime Vocation book written by Kurniawan et al. (2023). The book contains 33 visual images. The analysis has revealed that the representational modes with non-human picture were more prevalent. The finding shows that the visual images in this textbook are related to the objects that the students in Maritime Industry vocational school learn. In terms of interactive modes, visual images in this textbook use a lot of long-shot and oblique perspective. Additionally, the book predominantly utilizes color to enhance materials, accompanied by contextualization pictures depicting actual events. Then, for the compositional mode, illustrative images have an enormous value, providing concrete evidence so readers can understand the picture more effectively. The findings implied that this ESP textbook has a precise function for educational material and contains educational value for English in Maritime Industry which makes this book suitable because the visual images in this book show the real situation of the professional world. This study could help ESP teachers develop their content knowledge skills and understand the value of images in language learning by selecting images aligned with the pedagogical objectives.